Quantifying the contribution of hosts with different parasite concentrations to the transmission of visceral leishmaniasis in Ethiopia. - Ezer Miller; Alon Warburg; Ilya Novikov; Asrat Hailu; Petr Volf; Veronika Seblova; Amit Huppert (Public Library of Science (PLoS), 2014)
BACKGROUND: An important factor influencing the transmission dynamics of vector-borne diseases is the contribution of hosts with different parasitemia (no. of parasites per ml of blood) to the infected vector population. Today, estimation of this contribution is often impractical since it relies exclusively on limited-scale xenodiagnostic or artificial feeding experiments (i.e., measuring the proportion of vectors that become infected after feeding on infected blood/host). METHODOLOGY: We developed a novel mechanistic model that facilitates the quantification of the contribution of hosts with different parasitemias to the infection of the vectors from data on the distribution of these parasitemias within the host population. We applied the model to an ample data set of Leishmania donovani carriers, the causative agent of visceral leishmaniasis in Ethiopia. RESULTS: Calculations facilitated by the model quantified the host parasitemias that are mostly responsible for the infection of vector, the sand fly Phlebotomus orientalis. Our findings indicate that a 3.2% of the most infected people were responsible for the infection of between 53% and 79% (mean - 62%) of the infected sand fly vector population. SIGNIFICANCE: Our modeling framework can easily be extended to facilitate the calculation of the contribution of other host groups (such as different host species, hosts with different ages) to the infected vector population. Identifying the hosts that contribute most towards infection of the vectors is crucial for understanding the transmission dynamics, and planning targeted intervention policy of visceral leishmaniasis as well as other vector borne infectious diseases (e.g., West Nile Fever).